Adobe Photoshop Lightroom 2 : a Digital Photographer's Guide - Huss, David; Plotkin, David (Focal Press, 2008)
Adobe Photoshop Lightroom has taken the photography world by storm! Let two industry experts, Dave Huss and David Plotkin, help you get up to speed fast with the all-new version 2. This complete reference for all users of Lightroom starts out with the basics, covering each available tool found in Lightroom with step-by-step clarity. The book then moves on to more in-depth discussions of the most often used tools and techniques, so you can customize a workflow that best suits your own needs. Start at the beginning to develop a complete set of Lightroom skills, or skip ahead to the sections that delve deeper into the tools you want to use immediately. Learn how to work smarter, faster, and more creatively to improve the overall quality of your work so you can spend less time in front of the computer and more time behind your camera! Maximize your productivity and learn from two experts exactly how to incorporate Adobe Photoshop Lightroom into your own workflow, whether you use Windows or a Mac Fully up-to-date with the latest features of Lightroom 2 and packed with full color, step-by-step screenshots and photographs.